ANALISIS MANAJEMEN SYARIAH FAKTOR – FAKTOR YANG MEMPENGARUHI PENINGKATAN PENJUALAN ONLINE DI MASA PANDEMI COVID-19 (STUDI KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR) - Siti Yansi Apriyanti; Rully Trihantana; Ermi Suryani (SAHID BUSINESS JOURNAL, 2022)
The exixtence of this research is the background for the analysis of sharia management factors that affect the increase in online sales during the covid – 19 pandemic which aims (1) to analyze and find out how sharia management alyzes the factors that partially influence online sales (2) to analyze and knowing that promotions have a partial effect on increasing online sales. The methode used in this study is a quantitative method. The results of this research are linear regression equation Y= 1.588 - 0,123X1 + 0,294X2 + 0,046X3 + 0,619X4 + e. Promotional research partially provides answers that have a positive effect. That the value of the T-test results is 6.078 > T value is 1.993 and significant is 0.709 meaning H is rejected and H is accepted. Service quality has a partial efffect on increasing online sales with the F test value of 66,087 > F value of 2,734. So H is rejected and H is accepted means that there is an influence between the variables of production quality, price, promotion and service quality simultaneously on the variables of increasing online sales. The dominant variable influencing this research is promotion with a value of 6.078.